Islamic literary works in building personality as wasilah to preachers - Kamarudin, Kamariah (Human Resource Management Academic Research Society, 2020)
The relationship between literary works and readers is very close as it plays the role as wasilah of goodness in life. This is due to the huge responsibilities held by authors in delivering useful messages to people. The literary work is not mere entertainment but also a medium of da’wah in conveying the kindness, truth and beauty of religion. In fact, this has to do with the formation of readers’ personality especially among youth. Thus, inspiration in the work becomes the main subject as a support of an author. In line with that, from Ibn Qayyim’s view, inspiration from the perspective of al-Huda (direction) and al-Rashad (guidance) is needed in an author to deliver useful messages to readers. This paper will explore the role of da’wah in Islamic literary work based on da’wah bi al-Qalam to form the readers’ personality. Based on the study, it clearly shows that da’wah bi al-Qalam is necessary for an author in delivering useful messages and developing good personality.